The Essence of the Concepts of "Territory" and "Region" (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
The article discusses the term "region" and its origin. Various priority components of the region are also highlighted. And the concept of regional development, growth and development of public administration at the regional level is defined. Scientific approaches to the definition of the concept of "economic mechanism" and its principle construction have been developed.